The low-luminosity Type II SN 2016aqf: a well-monitored spectral evolution of the Ni/Fe abundance ratio. Issue 1 (6th July 2020) - Müller-Bravo, Tomás E; Gutiérrez, Claudia P; Sullivan, Mark; Jerkstrand, Anders; Anderson, Joseph P; González-Gaitán, Santiago; Sollerman, Jesper; Arcavi, Iair; Burke, Jamison; Galbany, Lluís; Gal-Yam, Avishay; Gromadzki, Mariusz; et al.
ABSTRACT: Low-luminosity Type II supernovae (LL SNe II) make up the low explosion energy end of core-collapse SNe, but their study and physical understanding remain limited. We present SN 2016aqf, an LL SN II with extensive spectral and photometric coverage. We measure a V -band peak magnitude of −14.58 mag, a plateau duration of ∼100 d, and an inferred 56 Ni mass of 0.008 ± 0.002 M⊙ . The peak bolometric luminosity, Lbol ≈ 10 41.4 erg s −1, and its spectral evolution are typical of other SNe in the class. Using our late-time spectra, we measure the [O i ] λλ6300, 6364 lines, which we compare against SN II spectral synthesis models to constrain the progenitor zero-age main-sequence mass. We find this to be 12 ± 3 M⊙ . Our extensive late-time spectral coverage of the [Fe ii ] λ7155 and [Ni ii ] λ7378 lines permits a measurement of the Ni/Fe abundance ratio, a parameter sensitive to the inner progenitor structure and explosion mechanism dynamics. We measure a constant abundance ratio evolution of 0.081^+0.009_-0.010 and argue that the best epochs to measure the ratio are at ∼200–300 d after explosion. We place this measurement in the context of a large sample of SNe II and compare against various physical, light-curve, and spectral parameters, in search of trends that might allow indirect ways of constraining this ratio. We do not find correlations predicted by theoretical models; however, this may be the result of the exact choice of parameters and explosion mechanism in the models, the simplicity of them, and/or primordial contamination in the measured abundance ratio.